2003
DOI: 10.1074/jbc.m302326200
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the Molecular Chaperone Hsp70 in Detergent-resistant Microdomains Correlates with Its Membrane Delivery and Release

Abstract: Accumulating evidence suggests that some heat shock proteins (Hsps), in particular the 72-kDa inducible Hsp70, associate to the cell membrane and might be secreted through an unknown mechanism to exert important functions in the immune response and signal transduction. We speculated that specialized structures named lipid rafts, known as important platforms for the delivery of proteins to the cell membrane, might be involved in the unknown mechanism ensuring membrane association and secretion of Hsp70. Lipid r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

28
222
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 281 publications
(251 citation statements)
references
References 26 publications
28
222
1
Order By: Relevance
“…HSP70 release from epithelial cells is mediated by sphingolipid-cholesterol-rich structures named lipid rafts [11]. To study the mechanism of oxLDL-induced HSP70 release in human macrophages, the cells were depleted of cholesterol using methyl-β-cyclodextrin before oxLDL treatment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…HSP70 release from epithelial cells is mediated by sphingolipid-cholesterol-rich structures named lipid rafts [11]. To study the mechanism of oxLDL-induced HSP70 release in human macrophages, the cells were depleted of cholesterol using methyl-β-cyclodextrin before oxLDL treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have shown that HSP70 can be actively released from cultured cells via a mechanism suggested to involve lipid-rafts [11,26,27]. A recent study has demonstrated that this also occurs in mononuclear cells [28].…”
Section: Discussionmentioning
confidence: 99%
“…Hsp70 has also been shown to associate with lipid rafts (Broquet et al 2003). These lipid-based organizational platforms, enriched in glycosphingolipids and cholesterol, are located in plasma membranes and have been implicated in a number of biological functions including membrane trafficking and signal transduction (Simons and Ikonen 1997;Hanzal-Bayer and Hancock 2007;Patra 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, transport [37,40] would require either increased cell membrane permeability [29] or a specific exocytotic pathway, as already was reported from a hepatosplanchnic source [28] and from the brain [45] following body exercise. A possible way of specific exocytotic transport via an alternative vesicular pathway not involving the endoplasmic reticulum-Golgi compartment was already reported [13]. This alternative transport of Hsp70 may occur either through lipid rafts or through exosomes [44].…”
Section: The Origin Of Salivary Chaperone Hsp70mentioning
confidence: 99%